Unmet Long-Term Care Needs: An Analysis of Medicare-Medicaid Dual Eligibles - Harriet L. Komisar; Judith Feder; Judith D. Kasper (SAGE Publishing, 2005)
People who are dually eligible for Medicare and Medicaid are the focus of fiscal struggles between federal and state governments. Drawing on a survey of community-based elderly "dual eligibles," this paper examines how well their medical and long-term care needs are being met under the current combination of Medicare and Medicaid policies. While few people report difficulty getting medical care, 58% of people needing long-term care (help with activities of daily living) report unmet needs. As a result, many experience serious consequences, such as falls. Although unmet needs are substantial in all six states surveyed, we find the greater the use of paid home care in a state, the lower the likelihood of unmet needs, suggesting states' policies can make a difference.